Esempi di rappresentazione degli omosessuali nella Commedia di Dante - Artico, Davide (Romanica Silesiana)
<!–EndFra–>Selected Representations of Homosexuality in Dante’s Commedia Since its very beginning, ‘the Queer’ as a cognitive construction in academic studies has been characterised by a certain degree of resistance to definition. The reluctance to have its traits encompassed by precise borders mirrors the very theoretical perspective ‘the Queer’ moves from, that is, one from which every strict classification appears to be hermeneutically reductive. Nonetheless, literature as a means of expression undoubtedly presents identification benchmarks for ‘the Queer.’ That is true for Italian literature as well, in which homosexuality, for instance, has been (re)presented since Dante Alighieri’s Commedia. The analysis of three Cantos performed here is aimed at providing a starting point for future diachronical studies whose purpose is to compare the approach to the theme in the Italian literature of the Middle Ages to the benchmarks emerging from the 20th century’s production, in whose mainframe an evolution in representation of ‘the Queer’ is made patent in the passage from Pasolini’s prose of the Sixties to the works by later authors such as Franco Buffoni and Pier Vittorio Tondelli. Key words: homosexuality in Dante’s Commedia.